Sensory Experiences and the Construction of Space in the Early Reign of Queen Maria Carolina of Naples-Sicily - Singerton, Jonathan (Österreichische Zeitschrift für Geschichtswissenschaften, 2022)
This article explores the construction of spaces through the senses of Maria Carolina, queen of Naples-Sicily. The rotation of courtly and private life between different environs of the Neapolitan capital region created frequent spatial change in the life of Maria Carolina between 1768 and 1799 – the period from her arrival as queen consort in Naples to the moment of her first flight from revolutionary outbreak. Her royal progresses throughout the environment around the city of Naples, routinely visiting various palaces and residences, allows for an analysis of sensory factors in the evolution of a spatial hierarchy for the queen. Regular movement between these places, it is argued, enabled a particular association with each space defined largely by positive and negative remembrances of the senses. In addition, her mobility included imagined journeys through the sensation of object perception and recalling sensory memories associated with such items. In discussing these aspects of her awareness and mobility, the relationship between sensory experience and spatial practice becomes a clear factor within the functionality of early modern courts.